Transcriptome analysis reveals molecular mechanisms underlying salt tolerance in halophyte Sesuvium portulacastrum - Wang, Dan; Yang, Nan; Zhang, Chaoyue; He, Weihong; Ye, Guiping; Chen, Jianjun; Wei, Xiangying (Frontiers in Plant Science, 2022)
Soil salinity is an important environmental problem that seriously affects plant growth and crop productivity. Phytoremediation is a cost-effective solution for reducing soil salinity and potentially converting the soils for crop production. Sesuvium portulacastrum is a typical halophyte which can grow at high salt concentrations. In order to explore the salt tolerance mechanism of S. portulacastrum, rooted cuttings were grown in a hydroponic culture containing ½ Hoagland solution with or without addition of 400 mM Na for 21 days. Root and leaf samples were taken 1 h and 21 days after Na treatment, and RNA-Seq was used to analyze transcript differences in roots and leaves of the Na-treated and control plants. A large number of differentially expressed genes (DEGs) were identified in the roots and leaves of plants grown under salt stress. Several key pathways related to salt tolerance were identified through KEGG analysis. Combined with physiological data and expression analysis, it appeared that channels cyclic nucleotide gated channels (CNGCs) were implicated in Na uptake and Na+/H+ exchangers (NHXs) were responsible for the extrusion and sequestration of Na, which allowed to maintain a balance between Na+ and K+ in S. portulacastrum under salt stress. Soluble sugar and proline were identified as important osmoprotectant in salt stressed S. portulacastrum plants. Glutathione metabolism played an important role in scavenging reactive oxygen species. Results from this study show that S. portulacastrum as a halophytic species possesses a suite of mechanisms for accumulating and tolerating a high level of Na, thus it could be a valuable plant species used for phytoremediation of saline soils.